PENGARUH PERPUTARAN KAS, PIUTANG, DAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN KONSTRUKSI YANG LISTING DI BURSA EFEK INDONESIA - Andi Zulfikar Syukriadi; Lukman Chalid (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aims to analyze (1) the effect of cash turnover on profitability, (2) the effect of receivable turnover on profitability, and (3) the effect of inventory turnover on profitability in pharmaceutical companies listed in Indonesia Stock Exchange.The results showed that together the three independent variables, which consist of cash turnover, receivable turnover, and inventory turnover have a positive and significant effect on the profitability of the company, which is shown through the value of Fhitung = 4.057 and Probability (sig) = 0.014 <0.050. Similarly, the contribution or contribution of the three independent variables is very large on the profitability of the company. This is indicated by the magnitude of the coefficient of determination (R2) = 0.253 or 25.30%. While equal to 0.747 or 74.70% influenced by other variables that are not used as variables in this study. The result of regression coefficient also shows that the cash turnover and inventory turn over each have a positive and significant effect on profitability, while receivable turnover has a negative and insignificant effect on the profitability of Construction companies listed in Indonesia Stock Exchange